Implementation of Management Standards (Case Study of Management Standards in Accreditation Assessment at PKBM Sejahtera Pontianak East Institute) - Muhammad Saleh Mahmud; Wahyudi Wahyudi; Muhammad Chiar (STKIP Singkawang, 2018)
This study aims to reveal information relating to (1) the leadership profile of the head of the management of the Community Learning Center (PKBM) Prosperous Center; (2) Work plan for accreditation management standards in PKBM Sejahtera institutions; (3) Organizing accreditation management standards in PKBM Sejahtera institutions; (4) Implementation of management of education units in PKBM Sejahtera institutions; (5) Supervision of education units in PKBM Sejahtera institutions; and (6) Reporting of the results of activities at PKBM Sejahtera institutions. The approach in this study uses a qualitative approach to the type of case study research. The results obtained from this study are the first chairman of the new prosperous PKBM has a D3 certificate in Civil Engineering and has 13 types of training/workshop / technical guidance certificates that are relevant to PKBM, and PKBM Sejahtera already has a community representative forum. Second, PKBM prosperous has clear and realistic vision, mission, and unit objectives, assisted villages / urban village that are in accordance with the vision, mission and objectives, long-term strategic plan (5year work plan), operational plan (annual work plan) clear; plan for the use of funds for a period of 5 years, already carrying out identification of community learning needs (IKBM) before determining the type of service program, already using the IKBM results as the basis for determining the type of service program; has included community members / leaders / RT heads, RW leaders (representing the community) in each service program preparation. Third, PKBM Sejahtera already has an institution's board posted/posted on the front fence but, the standard size has not been fulfilled all elements/explanations of certain activities in it, and there is no Tut Wuri Handayani symbol and has a network with 4 or more partner institutions in Last two years. Fourth, PKBM Sejahtera already has an activity schedule for each structured activity and unstructured activities, already has a list of participants in each study group (groups of students) for each type of service program, and already has a continuous service program so that there is no free time in each year. Fifth, PKBM Sejahtera has carried out monitoring and evaluation of service programs that are held regularly, has carried out monitoring and evaluation of learning by periodic managers and PKBM prosper does not make monitoring and evaluation reports. Sixth, PKBM prosperous has made a report on the results of each activity's complete activities, making a complete financial report after each activity, making a report on the results of its activities and finances supplemented by four documents of financial transactions consisting of bank accounts, cash books, diaries, documents financial transactions. As well as prosperous PKBM has submitted periodic reports of activity and financial results to the Pontianak City Education Office, Ditjen PAUD and Dikmas as well as agencies that provide assistance.